2010
DOI: 10.1007/s10903-010-9389-6
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Rural Immigrant Latino Youths’ and Adults’ Knowledge and Beliefs about Mental Health Resources

Abstract: Background-Immigrant Latino youth experience mental health problems in the U.S. Cultural beliefs and knowledge may influence help-seeking behaviors.Methods-Two hundred thirty-four immigrant Latino respondents between 12 and 44 years of age completed a questionnaire assessing knowledge of and cultural beliefs regarding mental health resources for adolescents, symptoms, and help-seeking.Results-Multivariate analyses showed that rural respondents were significantly less likely to know of mental health resources t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…Another common barrier was lack of knowledge about mental health services (37,56,75,77,78). In one study, fewer than 25% of all respondents indicated knowledge of mental health resources (78), and another study reported that 35% of immigrants were unaware that they had a diagnosable mental disorder (75).…”
Section: Resultsmentioning
confidence: 99%
“…Another common barrier was lack of knowledge about mental health services (37,56,75,77,78). In one study, fewer than 25% of all respondents indicated knowledge of mental health resources (78), and another study reported that 35% of immigrants were unaware that they had a diagnosable mental disorder (75).…”
Section: Resultsmentioning
confidence: 99%
“…For individuals who had used any prescription drug nonmedically -opioids, anxiolytics, or stimulants -we found that correlates of physician source of any prescription drug used nonmedically included characteristics such as older age, having insurance or having prescription drug dependence. These characteristics may reflect that these individuals are more likely to interface with physicians (17,40).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies examining rural racial/ethnic minorities and their use of illicit drugs suggested differences in prevalence, risk factors and patterns of use (15,41,42). Rural minority subgroups differentially access preventive healthcare services as compared to their urban counterparts (43)(44)(45). The interplay between race/ ethnicity, rurality and overdose requires more research to explore the finding that individuals who have died from prescription overdoses have predominantly been white rural residents (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Latino migrants tend to underutilise mental health services for a variety of reasons, including stigma, lack of medical insurance, lack of knowledge, and other access issues (Garcia et al 2011; Manoleas 2008; Nadeem et al 2007). These findings highlight the need for improved attention to mental health among migrants as a risk factor for HIV, especially in a new destination such as NC where many migrants experience isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%